2005
DOI: 10.1093/aje/kwi236
|View full text |Cite
|
Sign up to set email alerts
|

Decrements in Lung Function Related to Arsenic in Drinking Water in West Bengal, India

Abstract: During 1998-2000, the authors investigated relations between lung function, respiratory symptoms, and arsenic in drinking water among 287 study participants, including 132 with arsenic-caused skin lesions, in West Bengal, India. The source population involved 7,683 participants who had been surveyed for arsenic-related skin lesions in 1995-1996. Respiratory symptoms were increased among men with arsenic-caused skin lesions (versus those without lesions), particularly "shortness of breath at night" (odds ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 29 publications
8
111
0
Order By: Relevance
“…We also made novel observations that betel nut use and low BMI seem to adversely impact lung function in arsenic-exposed population. Consistently, three earlier studies from India and Pakistan observed that high levels of WA were associated with impaired lung function in populations that rely on groundwater (13)(14)(15). A few past studies also reported adverse respiratory outcomes (10,11,15,30) in persons with skin lesion from arsenic-affected areas of Bangladesh and India.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We also made novel observations that betel nut use and low BMI seem to adversely impact lung function in arsenic-exposed population. Consistently, three earlier studies from India and Pakistan observed that high levels of WA were associated with impaired lung function in populations that rely on groundwater (13)(14)(15). A few past studies also reported adverse respiratory outcomes (10,11,15,30) in persons with skin lesion from arsenic-affected areas of Bangladesh and India.…”
Section: Discussionsupporting
confidence: 64%
“…For instance, a study from India reported decreased FEV 1 (271 ml) and FVC (304 ml) among male smokers compared with nonsmokers (15). A retrospective study from Chile also found a strong effect of arsenic exposure on lung function impairment among nonsmokers who were exposed to arsenic early in life (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…98 Furthermore, in the same area, another study using a cohort of 287 participants who were exposed to 500 mgL À1 of arsenic, levels well above the current World Health Organization recommended maximum of 10 mgL À1 , reported a significant association between skin lesions and reduced lung function. 99 There is a growing body of evidence that shows that ingestion of arsenic through drinking contaminated water leads to significant chronic nonmalignant lung disease including obstructive and restrictive lung disease and bronchiectasis. 100 …”
Section: Water Pollution Arsenicmentioning
confidence: 99%
“…Peripheral vascular disturbances, dark abrasions on the feet (black foot disease), (Tseng et al 1968;Tseng 1977;Simeonova and Luster 2004), peripheral nervous system effects (Yamashita et al 1972;Dakeishi, Murata, and Grandjean 2006), diffuse pulmonary fibrosis, and bronchopulmonary Toxicologic Pathology, 43: 704-714, 2015 Copyright # 2015 by The Author(s) ISSN: 0192-6233 print / 1533-1601 online DOI: 10.1177/0192623314566240 lesions (Rosenberg 1974;Borgoño et al 1977;von Ehrenstein et al 2005) can also be diagnosed.…”
Section: Introductionmentioning
confidence: 99%